Implementation Thariqah Musykilah in Learning Qawaid in Syarqi Class Tsani Markaz Arabiyah Pare - Millah, Sholeh Najmul; Latifi, Lutfia Nasrul (Borneo Journal of Language and Education, 2023)
Learning qawaid to this day is still a scary specter for Arabic language students. In the minds of students, a stigma has arisen that learning qawaid is very complicated and boring. This is certainly caused by several factors, among which is the lack of innovation and creativity of a teacher in teaching. Therefore, in this article, the researcher will analyze tariqah musykilah in learning qawaid in the Syarqi Tsani Markaz Arabiyah Pare, which is judged to be capable of producing an interesting learning process and optimal learning outcomes. This research uses a qualitative field approach. The data used in this research is in the form of primary and secondary data. Primary data is sourced from observations, interviews, and documentation. While secondary data is sourced from books, journals, and articles related to this theme. The results of this research show that tariqah musykilah is able to create an effective learning process and make students more active and participative in class. In addition, tariqah musykilah is also able to make students understand qawaid in depth and in detail.